KERANCUAN ISTILAH KARAKTER, AKHLAK, MORAL DAN ETIKA - Reksiana Reksiana (Fakultas Adab dan Ilmu Budaya UIN Sunan Kalijaga Yogyakarta, 2018)
In academic world, the terminology of character, akhlak, morals and ethics are often equated. However, it will be differentiated. This paper will elaborate comprehensively both in perspective of the derivation of the words, theory, related science and its implementation in education. Among some experts who have different arguments such as Althof, Berkowitz and Victor Battistich differentiate these fourth terminologies in terms of theory and implementation. Both of these figures state that if moral and ethical theory is derived from philosophical theory. On its implementation, moral education tends to have a narrower scope, for instance only on cognitive development while character education has wider and comprehensive scope. In addition, Yoke Suryadarma and Ahmad Hifdzil Haq state the difference of these the fourth terminologies in the barometer and its implementation. The argument of these two figures refers to the opinion of Imam Al-Ghazali, who states that morality is not merely acts, or just the ability to do, not just knowledge also. However, moral is an effort to integrate akhlak with the situation of the soul who are ready to bring up good and bad deeds, not just for a moment but forever. This article exerts a descriptive analysis approach, which is based on analyzing all the fourth related terminology arguments in the perspective of the derivation of the word, theory, related science and its implementation. Keywords: Character, ecthic, attitude and terminologi of character